2007
DOI: 10.1002/app.25103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of TRITON™ X‐based surfactants with carboxylic or amino groups in the oxyethylene chain end

Abstract: This paper describes the synthesis and characterization of a series of TRITON TM X-based surfactants with a predominantly alkyl phenol ethoxylate (APE) backbone and carboxylic or amino chain ends. Three carboxylic acid-containing TRITON X (or APE)-derivatives, [OPE2-COOH], [OPE5-COOH], and [OPE10-COOH], were prepared from commercially available octyl phenol ethoxylate (OPE) of different oxyethylene units (i.e., n ¼ 2, 5, and 10) and ethyl bromoacetate via a simple etherification reaction followed by saponifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The synthesis and characterization of Triton X derivatives containing specially added acidic or basic moieties were reported earlier by our group 11. We also demonstrated that a Triton X based compound with a terminal carboxylic acid (OPE–COOH) could be a better dispersant than others that have ester, phosphoric acid, or amino‐functional groups 12.…”
Section: Introductionsupporting
confidence: 64%
“…The synthesis and characterization of Triton X derivatives containing specially added acidic or basic moieties were reported earlier by our group 11. We also demonstrated that a Triton X based compound with a terminal carboxylic acid (OPE–COOH) could be a better dispersant than others that have ester, phosphoric acid, or amino‐functional groups 12.…”
Section: Introductionsupporting
confidence: 64%
“…On the other hand, it seems sensible to place the reactive group in the hydrophobic moiety of the surfmer [27]. Lee et al [28] reported on the synthesis and characterization of a series of surfactants with a predominantly alkyl phenol ethoxylate (APE) backbone and carboxylic or amino chain ends. In this study, we attempted to introduce the carboxylic acid group (or anhydride groups) into the oxyethylene chain end of polymerizable APEs to increase the functionality and polymerizable bonds and to increase the surface activity of these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the APE surfactants are soluble in various aqueous and organic solvents, but they are partially soluble in basic aqueous solutions [28]. However, NME and NMA are soluble in basic and acidic aqueous solutions.…”
Section: Solubility and Surface Activitymentioning
confidence: 99%
“…In our group, various types of sophisticated dispersants (e.g., Triton derivatives) are often employed as a viscosity modifying agent. 9,10 Synthesized acrylic dispersants with well-defined compositions have captivated both academic and industrial polymer engineers. Recent works have been done to improve the modification of classical syntheses toward more precisely controlled acrylic backbones, which are required in the design of advanced dispersants.…”
Section: Introductionmentioning
confidence: 99%